Assessment of linguistic comfort in the urban space of the northern and Arctic cities - Bitkeeva, Aysa N.; Khokholova, Irena S.; Filippova, Viktoria V. (The New Research of Tuva, 2025)
The article presents the development of a toolkit for assessing linguistic comfort in urban space, which is applied to the case of a northern and Arctic city. Linguistic comfort is understood as the ease and necessity of using languages — components of the city’s socio-communicative system — in everyday life, as well as the presence of conditions for their harmonious co-functioning and broad functional distribution. The study is based on comprehensive research of the linguistic landscape in the Republic of Sakha (Yakutia) — the cities of Yakutsk and Mirny — and in the Chukotka Autonomous Okrug — the cities of Anadyr and Bilibino (2023–2024), involving a survey of 800 urban residents and interviews with 41 individuals. The toolkit enables a detailed analysis of the interrelation of sociocultural factors that are key in shaping the urban environment: the proximity of the urban community to nature, historical, political, and economic factors, demographic, communicative, and symbolic capacities, as well as linguistic competition or monopoly, language ideologies, and language activism under northern conditions, among others. It has been established that the level of linguistic comfort in urban space is determined by the interdependence of legal and administrative support, the activity of the urban community and language activists, a scientifically grounded approach to addressing language issues, and the broader social climate.